MANAGEMENT OF A CASE OF LUMBAR STENOSIS WITH AYURVEDIC INTERVENTION - Kshirod Kumar, Ratha; Laxmi Dhar, Barik; Jayram, Hazra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Ayurveda intervention is gaining popularity for chronic and degenerative disorders. Lumbar stenosis is narrowing of spaces of lumbar spine cause morbidity in old age. Surgical laminectomy is the only answer in conventional therapy. However, the disease can be better managed in Ayurveda through panchakarma and rasayana treatment. Keywords: Low back pain, Lumbar stenosis, Panchakarma, Katigraha.